Stakeholder-Formed Organizations and Crisis Communication: Analyzing Discourse of Renewal with a Non-Offending Organization (Journal of International Crisis and Risk Communication Research, 2020)
Scholars have examined the ways organizations practice post-crisis communication strategies, including deny, diminish, and rebuild. The current study explores the extent to which a stakeholder-formed organization utilizes post-crisis discourse of renewal to rebuild, recover, and renew the Catholic Church after allegations of sexual abuse of minors publicly surfaced in the United States. Open-ended semi-structured interviews with founders and executive committee members of Leadership Roundtable revealed stakeholders practiced discourse of renewal to help the Catholic Church, an offending organization, recover from a crisis. This study also assessed the extent to which God and religion motivated stakeholders’ responses. Results suggest religion is a critical motivating factor in stakeholders’ responses to a crisis.